Local Wisdom in Indonesia: Assessing its Legal Status and Role in Forest Protection - Helmi, Helmi; Pebrianto, Dony Yusra; Hafrida, Hafrida; Kusniati, Retno; Saputra, Beny (Jambe Law Journal, 2023)
This study delves into an examination of the role played by local wisdom in the protection of forests. The recognition and acknowledgment of local wisdom, enshrined in customary law within the environments of indigenous peoples, encounters challenges, particularly when the legitimacy of customary law itself is in question, especially concerning forest protection. In addressing these concerns, a normative juridical approach was employed to scrutinize legal source materials. The findings of this research affirm that the recognition of indigenous peoples as legal entities, particularly under international law, necessitates collective consideration. Through this conceptual framework, indigenous peoples can assert their aspirations autonomously and even advocate for international policies aimed at safeguarding and upholding the rights of indigenous peoples globally, with predetermined terms and conditions. The study underscores the contribution of local wisdom to forest protection, exemplified by the formulation of customary forest concepts applicable to indigenous communities. Local wisdom has demonstrated efficacy in averting and mitigating forest damage, particularly within customary forest areas, owing to the steadfast adherence of indigenous peoples to the principles encapsulated in their customary law. Moreover, the effectiveness of local wisdom in forest preservation is bolstered by the intrinsic characteristics of traditional indigenous communities, fostering wise and sustainable forest management practices. The study posits that the normative nature of customary law, as a living legal entity, may face ineffectiveness, potentially jeopardizing its own existence. Nonetheless, it contends that the state should formally recognize the exclusivity of customary law through constitutional and legal frameworks, thereby fortifying the application and viability of customary law within predetermined geographical areas and communities designated by the government